Radicular cyst associated with odontogenic maxillary sinusitis in CBCT study: Radicular cyst associated with odontogenic maxillary sinusitis in CBCT study - Ifa ariefah; Barunawaty Yunus; Fadhlil UA Rahman; Yossy Yoanita A (Makassar Dental Journal PDGI Makassar, 2024)
Radicular cysts are one of the most common types of cysts that occur in the jawbone, which in the maxilla, may invade into the sinuses. The CBCT radiographs make it easier for dentists to evaluate the boundaries and extension of the cyst lesion. This case report analyses the expansion of a radicular cyst into the maxillary sinus area causing maxillary sinusitis. A 58-year-old man com-plained of gingival swelling of the left maxilla that occurred in the area of the retained root of tooth 23, and extended to the right maxillary sinus. After CBCT-3D scanning, an osteolytic lesion was found at the periapical area of teeth 22 and 23, which extend-ed to the maxillary alveolar bone and caused perforation at the base of the left maxillary sinus with hyperpigmented appearance along the sinus base on radiographs. The patient underwent cyst enucleation, fistulectomy, sinus washing, and multiple tooth extractions. Biopsy of the lesion showed the character of a radicular cyst. It was concluded that CBCT imaging clearly showed the extension of the maxillary radicular cyst lesion to the maxillary sinus to support an appropriate treatment plan.